Characterization of the Distal Esophagus High-Pressure Zone with Manometry, Ultrasound and Micro-Computed Tomography - Vegesna, Anil K. (2012)
BACKGROUND: We sought to determine how the individual components of the distal esophagus and proximal stomach form the gastroesophageal junction high-pressure zone (GEJHPZ) anti-reflux barrier. METHODS: An endoscopic ultrasound/manometry catheter was pulled through the proximal stomach and distal esophagus in 20 normal subjects. The axial length and width of individual structures on endoscopic ultrasound were measured. The anatomic orientation of gastroesophageal junction (GEJ) components was examined in two organ donor specimens using micro-computed tomography (micro-CT). KEY RESULTS: The three distinct structures identified within the GEJHPZ, from distal to proximal, were: the gastric clasp and sling muscle fiber complex, crural diaphragm, and lower esophageal circular smooth muscle fibers (LEC). The LEC was statistically significantly thicker than adjacent esophageal muscles. These structures were associated with 3 pressure peaks. The pressure peak produced by the clasp/sling fiber complex often overlapped with the pressure peak from the crural diaphragm. The most proximal peak, associated with the LEC, was significantly greater and bimodal in 9 of 20 subjects. This bimodal LEC pressure peak correlated with two areas of thickened muscle observed with ultrasound. Micro-CT of GEJ from organ donors confirmed the two areas of thickened muscle. CONCLUSIONS AND INFERENCES: Three distinct anatomic structures, the clasp and sling muscle fibers, crural diaphragm, and LEC combine to form the anti-reflux barrier of the proximal stomach and distal esophagus. The clasp and sling muscle fibers combine with the crural diaphragm to form a distal pressure profile. The more proximal LEC has a bimodal pressure profile in some patients.